Uighur college students' irony comprehension in Chinese. (August 2022) - Chen, Xiaoli; Li, Degao; Wang, Xiaolu
Aims and objectives/purpose/research questions: Irony comprehension can be more demanding than literal comprehension in L1. This study aimed to seek an answer to how bilinguals perform in L2 in irony comprehension. Design/methodology/approach: Totally, 85 Uighur College students participated in a self-paced reading task in Chinese, with 81 Chinese native speakers as the controls. In Experiment 1, a scenario was followed by a commentary statement in which the critical word either was literally congruent with the context in meaning or could only be ironically understood. In Experiment 2, the same statement was preceded by three sentences which were either literally consistent with the critical word or created a context for the critical word to be understood ironically. Data and analysis: ANOVAs were conducted on participants reading times (RTs) to the critical words and commentary statement endings in the 14 pairs of discourses. They did not have different RTs for the critical words across the ironic and non-ironic conditions in L1, but had significantly longer RTs in the ironic condition than in the non-ironic condition in L2. Their RTs for the commentary statement endings were significantly longer in the ironic condition than in the non-ironic condition in both experiments, regardless of whether the materials were presented in L1 or L2. Findings/conclusions: Irony comprehension is similar in L2 to how it is in L1. However, salient meaning retrieval (in Experiment 1) and inference-making (in Experiment 2) in irony comprehension, as assumed by the Graded Salience Hypothesis, were more likely to be revealed in L2 than in L1. Originality: This seems to be the first study in the native and non-native domain of irony processing in the procedure of discourse reading. Significance/implications: L2 learners should do as many practices as possible to improve their reading proficiency in the target language.